Pengaruh Frekuensi Pemberian Asam Salisilat dan Bradyrhizobium untuk Meningkatkan Produktivitas Edamame (Glycine Max L.Merr) di Lahan Gambut - Rona, Rona; Suswanto, Iman; Basuni, Basuni (Perkebunan dan Lahan Tropika, 2025)
Edamame has high yield potential; however, production in Indonesia remains limited. Edamame production on peatlands faces several obstacles, including the nature of peat, which often has low nutrient content and high acidity levels that do not support the formation of root nodules. One way to form root nodules to increase edamame productivity is to use salicylic acid and Bradyrhizobium bacteria. This study aims to determine the effects of the timing of salicylic acid and Bradyrhizobium treatment on edamame productivity in peatlands. This research was conducted in Siantan Hilir, North Pontianak, during July-September 2024. The experimental design used was a factorial RAL split-plot design consisting of two factors. The first factor is the treatment of Bradyrhizobium bacteria, and the second factor is the timing of salicylic acid treatment. There are six treatment combinations with 6 times replications. The variables observed include plant height, number of leaves, number of root nodules, root length, number of pods per plant, weight of pods per plant, yield per plot, and yield per hectare. The results showed no significant interaction between salicylic acid treatment and Bradyrhizobium bacteria. Salicylic acid treatment significantly affected the number of root nodules, number of pods per plant, weight of pods per plant, yield per plot, and yield per hectare. Still, it did not significantly affect plant height, leaf number, or root length. Bradyrhizobium bacteria treatment significantly affected the number of root nodules, number of pods per plant, weight of pods per plant, yield per plot, and yield per hectare. Still, it did not significantly affect plant height, leaf number, or root length. The treatment of salicylic acid and Bradyrhizobium bacteria individually had a significant effect on the number of root nodules, number of pods, pod weight, and yield per plot and per hectare.